Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
9514 1404 393
Answer:
(x, y) = (-1, -3)
Step-by-step explanation:
The equations are "consistent" and "not dependent." This will be the case whenever the ratios of x- and y-coefficients are different.
__
We can solve this by "elimination" by multiplying the first equation by -4 and adding the result of the second equation being multiplied by 7.
-4(2x -7y) +7(7x -4y) = -4(19) +7(5)
-8x +28y +49x -28y = -76 +35 . . . . eliminate parentheses
41x = -41 . . . . . simplify
x = -1 . . . . . . . divide by 41
Using the second equation, we find y to be ...
(7x -5)/4 = y = (7(-1) -5)/4 = -12/4 = -3
So, the solution is (x, y) = (-1, -3).
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.